Meningkatkan Motivasi Belajar Peserta Didik dengan Menggunakan Metode Quiz Team - Baiq Adila Pratiwi Rahman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to improve students’ learning motivation through the implementation of the Quiz Team method in a sixth-grade class at SDN 31 Mataram. The research employed a Classroom Action Research (CAR) approach conducted in two cycles following the Kemmis & McTaggart model, which includes planning, action, observation, and reflection. Data were collected through observations, motivation tests, and documentation. The results indicate that the Quiz Team method significantly increased students’ learning motivation. The average motivation score improved from 59.05 in the pre-test to 77.70 in the post-test, and the percentage of students who achieved learning completion from 0% to 60%. In addition to score improvements, students displayed more active participation in discussions, better focus, and higher enthusiasm during learning activities. Therefore, the Quiz Team method is effective as an alternative instructional strategy to enhance students’ learning motivation.